(untitled) (Global Journal of Management and Business Research, 2020)
Enterprise Resource Planning systems (ERP) have emerged as solutions oriented to manage organization´s resources in an integrated way. They allowed the automation of its department’s activities, made information available to users at the right time, supporting more accurately their decision-making needs. It is empirically proved that the best of the breed application for the optimum benefit of an organization is a mixture of both ERP and non-ERP application. Organizations faces lot of challenges while integrating these two application systems. ERP system uses world best practices and they uses better software development standards to develop the ERP application and to incorporate the application security. However, other application vendors do not follow the best practices for application development and do not incorporate optimum security to their application. Owing to these mismatches, the integration of ERP and non-ERP system become very challenging.